Output-Based Aid in India : Community Water Project in Andhra Pradesh - Mandri-Perrott, Cledan (World Bank, Washington, DC, 2012)
Providing safe drinking water to poor families in the coastal area of Andhra Pradesh is critical for the economic development of the region as well as to improve health and living conditions. A community water project supported by the Global Partnership on Output-Based Aid (GPOBA) is increasing innovation and efficiency in the sector through a community based public-private partnership model using cost-effective water purification technology. Enhancing the sustainability of pilot water projects in villages in Andhra Pradesh has been a key part of the project design. The scheme provides a performance based subsidy linked to the delivery of pre-agreed outputs which include three months of billed water services. The output-based approach requires that tariffs paid by users for consumption cover the costs of operation and maintenance, user-fee collection, and education and communication activities with key stakeholders and vulnerable groups such as young mothers, infants, and families living below the poverty line. Tariffs also cover loan repayment, thus helping to ensure the long-term sustainability of the services. The project has potential for replication in other villages in Andhra Pradesh and ultimately in other parts of India.